Interacting with Generative Music through Live Coding. - Brown, AndrewR.; Sorensen, Andrew (Contemporary Music Review, 2009)
All music performances are generative to the extent that the actions of performers produce musical sounds, but in this article the authors focus on performative interaction with generative music in a more compositional sense. In particular they discuss how live coding of music involves the building and management of generative processes. They suggest that the human interaction with generative processes that occurs in live coding provides a unique perspective on the generative music landscape. Especially significant is the way in which generative algorithms are represented in code to best afford interaction and modification during performance. They also discuss the features of generative processes that make them more or less suitable for live coding performances. They situate live coding practice within historical and theoretical contexts and ground the discussion with regular reference to their experiences performing in the live coding duo aa-cell.